Pengukuran Jarak Berdasarkan Ekstraksi Nilai Hue Pada Citra Depth Menggunakan Sensor Kinect - Hendawan Soebhakti (Politeknik Negeri Batam, 2012)
Distance measurement is the main requirement in a mobile robot navigation system. By knowing the distance to the object, the robot can maneuver to avoid the object. Today, the uses of vision sensors such as cameras become the first choice in mobile robot navigation system. By using the vision sensor, in addition to measuring the distance, shape and color of objects can also be known. In this research we used a Kinect sensor that can produce RGB and depth images. A polynomial equation can be established by measuring the change of hue value that proportional to distance. The results showed the average measurement error is 3.39% with accuracy of 1 cm.